(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
This article discusses the issues of developing the professional and psychological competence of future technological education teachers. The significance of theoretical knowledge and practical skills for technological education teachers, the formation of pedagogical mastery, and the main challenges encountered in the educational process are analyzed. Additionally, innovative methods and technologies used to enhance pedagogical skills and important recommendations for improving the quality of education are provided. The research results indicate that the effective organization of pedagogical practice and the development of specific methodological guidelines are crucial factors in increasing the professional and psychological preparedness of future technological education teachers.